Evaluation of the efficacy of 10% albendazole vermifuge through the analysis of coproparasitology and blood count in Nellore calves in the city of Buritis, Rondônia (Research, Society and Development, 2021)
As one of the main activities within the state of Rondônia and the country, cattle raising has enormous economic importance. One of the most damaging points for cattle raising is around endoparasitosis in calves in their early life, causing these animals to have a reduction in weight gain. To present the efficacy of the albendazole vermifuge, through the analysis of coproparasitology and blood count in Nellore calves was the objective of the present work. Demonstrating in a practical demonstrative way in 30 calves aged 2 to 3 months, of life in a period of 15 days divided equally into: Group I, control, and Group II, treatment, and, finally, stipulate a final average of eggs per gram of feces to evaluate the efficiency of the evermination with 10% Albendazole orally. Blood counts and coproparasitological tests were performed to show the hematological status of the animals and Eggs per Gram of Feces (OPG). To arrive at the result of effectiveness, the formula used was the calculation of Reduction in Egg Count per Gram of Feces. Thus, the effectiveness of the 10% Albendazol dewormer in calves between 2 and 3 months was 97.51%. Thus, considered effective, in accordance with the technical regulation of the Common Market Group (GMC). In the hematological context, it was observed on the fifteenth day, a relationship between a greater mean of eosinophils in the hemograms of the animals in the control group (high parasite load), compared to the everted animals (low parasite load).